ANALISIS KEGAGALAN POROS ROLL PADA MESIN PELET KAYU DENGAN METODE REDESIGN IMRC - Adhiharto, Riky; Rahmi, Meri; Hakim, Adies Rahman; Rafiq, M. Wildan A. (Jurnal Teknologi Terapan, 2025)
The wood pellet machine is one of the Special Purpose Machines (SPM) that has an important element as a driver. One of the damaged machine elements is the broken roll shaft due to long-term use. The roll shaft functions to hold the roll so that it does not rotate during the wood pelletizing process. Failure analysis was carried out on the roll shaft, starting with a redesign using the IMRC method. The stages of this method are incremental, elemental, and radical stages. The redesign strategy chosen was an incremental redesign. This redesign changes the core component but does not change the mechanism or function. The results obtained after the redesign, obtained changes in the dimensions of the roll shaft so that it does not break with a value above the permitted control value. The largest shaft diameter becomes 70 mm, the diameter at the critical part becomes 60 mm and the length of the spline construction becomes 50 mm. With this change in diameter, a safety factor for the shaft was obtained after the redesign with a value of 6.83 and is categorized as safe.